Analysis of the Content of the Science Book for the Primary Stage According to Theory of Multiple Intelligences (Journal Of Educational and Psychological Researches, 2024)
The current research aims to identify the degree of inclusion and distribution of indicators of multiple intelligences in the science book for the primary stage, represented by units of analysis (scientific material and activities together). To achieve the objective of the research, the analytical descriptive approach was used, the method of content analysis. The research sample consisted of the science books for the first three grades (the first primary, the second primary, and the third primary). The results of the research showed the inclusion of the two bits of intelligence (visual, spatial, and linguistic) was more than expected, while intelligence (logical, mathematical, physical, kinesthetic, natural, environmental, social, personal, and musical) was less than expected and was distributed in a way that disrupted their balance in the science book for the first three grades, except for not including intelligence musical in the science book for the second grade and also not including the two intelligences (social and musical) in the science book for the third grade. The current research has come up with a set of recommendations and suggestions